Atividade biológica e quantificação de compostos bioativos em extrato de erva mate e sua aplicação em hambúrguer de peixe - Tonet, Andressa (2017)
For thousand of years, plants have been natural sources of substances used in industry. An example of such plants is yerba mate, which in turn contains high content of biologically active compounds with potential industrial application. This paper aimed to assess the biological activity of yerba mate extract, to quantify its compounds and to apply in fish hamburger. The yerba mate dry extract was submitted to two different assays in order to evaluate the antioxidant activity. In the DPPH assay, IC50 results of 7.91 μg mL-1 for the yerba mate extract (YME) and 1.04 μg mL-1 for butyl hydroxyanisole (BHA) were observed. For the FRAP assay, the results of Fe (II) reduction per gram of sample were 4922.67 for YME and 15801.14 for BHA. The research of the antioxidant power of the combination of yerba mate and BHA was carried out by experimental design by the DPPH assay, in which the obtained results allow us to predict the response of each compound at predetermined concentrations. The assessment of the antimicrobial activity was carried out in isolation by the Minimum Inhibitory Concentration (MIC) assay and in combination with the checkerboard technique. The results obtained from MIC for YME against E.coli, S. aureus and Salmonella sp. were 10 mg mL-1, 5 mg mL-1 and 10 mg mL-1, respectively, and for BHA was 0.313 mg mL-1 for all assessed microorganisms. In regard to the interaction analysis of the compound combination, additive activity was observed, according to the calculated FIC index value of 0.998 for S. aureus. The methodology developed for the quantification of yerba mate compounds by ultra performance liquid chromatography (UPLC) was specific, linear, precise and accurate. The results of the compounds quantification by UHPLC were 49.6 mg g-1 of chlorogenic acid, 34.5 mg g-1 of caffeine and 23.1 mg g-1 of rutin. Finally, the fish hamburgers were prepared and the analyzes of centesimal composition, lipid and microbiological oxidation were carried out. No lipid oxidation was observed in the product. Regarding the microbiological analysis of mesophilic counts, statistic difference was observed between the control formulation and the formulations with BHA and 1.0% yerba mate extract. However, additional studies using yerba mate should be performed to prove its effective preservative power.